Synthesis of Scalar Control System of Asynchronous Motor Drive - B. I. Firago; O. F. Opeiko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Provision of quality indices is of great importance for motor drive in the case of parametric and external disturbances. The purpose of the paper is to make synthesis of a scalar control system of asynchronous motor drive that ensures the required quality indices in the specified range of parameter changes of a linearized electric motor model. Expressions have been obtained that make it possible to estimate change limits of main linear model parametersThe paper considers a structure of a closed loop system with dynamical output feedback and its derivative. A simulation has been executed for a calculative linear system and for a system with a simulating model of an asynchronous short-circuited electric motor at various laws of frequency control.The method provides the required dynamic indices at parametric and external disturbances occurring in the limited area.